A Struggle for Democracy in the Workplace : The Possibilities and Limits of the Constitutionalization of Labour and Employment Law in Brazil - Garcez, Maximiliano (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2007)
Workplace relations in developing countries are characterized as being traditionally authoritarian. But severe violation of human rights in the workplace can also be found in the most developed countries, and therefore modern society is finding itself faced with a sad reality : a universal situation of the vulnerability and fragility of human rights in the workplace. Through the weakening of state institutions and the corresponding strengthening of the economic power spheres within the context of globalization, the survival of democracy in everyday life is threatened by transnational corporations, especially considering the lack of instruments to appropriately punish them. The human rights movement in Brazil has focused on the violation of human rights perpetrated by governments, yet it has not been so critical or outspoken regarding violations committed by major corporations. Defending the implementation of human rights in the workplace is an effort to counteract the dehumanization of worker-citizens by giving them more space for self-determination. It is essential that the principle of human dignity, already enshrined in the Brazilian Constitution, becomes one of the main pillars of Labour and Employment Law. The article analyzes how the constitutionalization of Labour and Employment Law in Brazil has been used to tackle the above mentioned problems.